Periodontopathogen and Epstein–Barr Virus‐Associated Periapical Periodontitis May Be the Source of Retrograde Infectious Peri‐Implantitis. (15th May 2013) - Verdugo, Fernando; Castillo, Ana; Simonian, Krikor; Castillo, Francisca; Farez‐Vidal, Esther; D'Addona, Antonio
Abstract Background Herpesviral‐bacterial synergism may play a role in periodontitis and peri‐implantitis etiopathogenesis. Periapical periodontitis (PP) lesions can predict future apical peri‐implantitis complications. Purpose This pilot study aimed to substantiate herpesviral‐bacterial coinfection in symptomatic (SP) and asymptomatic (AP) PP and assess associations with periodontopathogen salivary contamination in patients receiving implants. Materials and Methods Polymerase chain reaction (PCR)‐based identification was performed on PP granulation tissue (GT) from 33 SP and AP patients and compared with unstimulated whole saliva. Quantitative PCR evaluated Epstein–Barr virus (EBV) and cytomegalovirus copy counts. Results SP GT had higher proportions of periodontopathogens. Symptomatic patients were 3.7 times more likely to be infected with EBV than AP (p = .07; 95% CI: 0.8–16.2). SP were 2.9, 2.1, 3.6, and 1.6 times more likely to be infected with Treponema denticola, Prevotella intermedia, Aggregatibacter actinomycetemcomitans, and Porphyromonas gingivalis, respectively. The odds ratio of EBV infecting PP lesions was two times higher in those positive for the virus in saliva. Saliva Tannerella forsythia‐positive patients were 15 times more likely to present this pathogen in PP lesions (p = .038). Saliva EBV‐positive individuals were 7 and 3.5 times more likely to yield GT contamination with T. forsythia and T. denticola, respectively. EBV copy counts were significantly higher in SP (p < .01). Conclusions A causal association between EBV, specific bacterial anaerobic infection, and symptomatic PP is likely. EBV high prevalence underscores the viral etiological importance. Salivary EBV contamination is likely to be associated with viral and bacterial GT infection. Saliva PCR analysis can be a good predictor of GT specific infection and help establish antimicrobial therapy. If confirmed by prospective longitudinal clinical trials, antiviral therapy could possibly benefit SP and nonresponsive to treatment individuals and help prevent potential peri‐implant infectious complications.